ЕКОЛОГІЧНІ НАСЛІДКИ ГІДРОБУДІВНИЦТВА НА ДНІПРІ (50 – 70-ті рр. ХХ ст.): ІСТОРІЯ І СУЧАСНИЙ СТАН ПРОБЛЕМИ (Zaporizhzhia Historical Review, 2021)
The article decides ecological consequences of hydroelectric power plants construction on the Dnipro in the 1950-s – 1970-s. The author defines the character of changes in the environment and analyses the possibility to overcome negative results. The article highlights the public and government attitude to the protection of nature.